Increased EEG Current-Source Density in the High Beta Frequency Band Induced by Levetiracetam Adjunctive Therapy in Refractory Partial Epilepsy - Park, Sung-Pa (Korean Neurological Association, 2009)
BACKGROUND AND PURPOSE: Levetiracetam (LEV) is an antiepileptic drug (AED) that has favorable effects on cognition. Although neuropsychological studies have demonstrated these favorable outcomes on cognition, there are few electrophysiologic data describing the functional changes exerted by LEV. The purpose of this study was to determine the effects of LEV adjunctive therapy on the current-source density (CSD) in the high beta frequency band (22-30 Hz) of EEG background activity in refractory partial epilepsy (RPE). METHODS: We conducted a 24-week, open-label, prospective study in 24 patients with RPE. Scalp electroencephalography and neuropsychological tests (NPTs) were conducted twice, once before the LEV trial and then again after 24 weeks of medication. RESULTS: The CSD in the 22-30 Hz band of EEG background activity increased in the bilateral anterior cingulate gyri, left parahippocampal gyrus, and a small area of the right anterior parahippocampal gyrus after the LEV trial. Neither seizure freedom nor the dosage increment of LEV elicited meaningful CSD changes. Verbal memory and executive function were improved after the 24-week LEV trial. CONCLUSIONS: To our knowledge, this is the first study to examine the changes in CSD induced by LEV adjunctive therapy in RPE patients. The CSD changes and NPT results suggest that LEV enhances the activities of the neuronal networks in the prefrontal cortex and left hippocampus.